Children's collaborative recall of shared and unshared information. (30th November 2012) - Gummerum, Michaela; Leman, Patrick J.; Hollins, Tara S.
<x xml:space="preserve">Abstract</x> This study examined age differences in collaborative inhibition and the role of inter‐subjectivity, collective information sampling (CIS) and collaborative inhibition for the collaborative recall of shared and unshared information in groups of 7‐ and 9‐year‐old children. Three‐hundred and thirteen 7‐ and 9‐year‐old children recalled memorized wordlists either in real or nominal groups of three. All group members either recalled the same items, or each group member was given some unique items. Nine‐year‐olds, but not 7‐year‐olds, recalled significantly more items in nominal than real groups, a phenomenon called collaborative inhibition. Groups whose interactions were characterized by higher numbers of inter‐subjective exchanges recalled fewer words than groups low in inter‐subjectivity. In both age groups, a higher proportion of shared compared with unshared information was recalled consistent with processes of CIS. However, 7‐year‐olds recalled more unshared items than predicted, suggesting that collaborative inhibition additionally contributes to the recall of shared and unshared items.